Expression profiling of the CHS8, CHI1A, IFS2, and CHR genes in black soybean seed [Glycine max (L). Merr.] of F4 generation - Dadang Sumardi; Aulia Marwah Mumtaza; Rijanti Rahaju Maulani; Adi Pancoro; Husna Nugrahapraja; Sony Suhandono; Tati Suryati Syamsudin; Agung Kurniawan (Universitas Gadjah Mada, 2019)
Black soybean [Glycine max (L.) Merr.] produces isoflavones as secondary metabolites, which have many benefits for human health and plant defense system. Expression profiling can guide potential work in functional genomics of the isoflavone biosynthesis pathway. Previous studies showed the vital role of the CHS8, CHI1A, and IFS2 genes in isoflavone biosynthesis. However, expression profiling of these genes in the local black soybean varieties is still limited. This study investigated the gene expression levels of the CHS8, CHI1A, IFS2, and CHR genes in local varieties, namely, UP106 (high isoflavone) and UP122 (low isoflavone) and its progenies, i.e., UP106xUP122 and UP122xUP106. Relative gene expression profiling was conducted on the basis of Reverse Transcriptase Polymerase Chain Reaction (RT‐PCR) with ACT2/7 as a housekeeping gene. As a result, the expression level of CHS8 in UP122 is lower than that in UP106. No significant difference in the expression level of CHI1A was observed in all samples. The expression levels of CHS8 and CHI1A in both progenies were higher than that in the parental line, whereas the expression levels of IFS2 in both progenies were lower than that in the parental line. CHS8 and IFS2 expression from UP106xUP122 was higher than that from UP122xUP106, whereas CHI1A expression from UP122xUP106 was higher than that from UP106xUP122. CHR showed a high expression in the reciprocal cross; however, this expression did not exceed from UP106. In conclusion, the crossing between parental lines did not affect the gene expression level in the isoflavone biosynthesis pathway.